Opto-electrical investigation of Zn metal-doped CdS and their application in soft lithographic technique - Hussain, Gulalai; Jabeen, Uzm; Hafeez, Irfan; Malghani, M Najam Khan; Mushtaq, Ayesha; Rizwan, Sabeena; Bashir, Farrukh; Behlil, Farida; Raza, M Aamir; Anjum, Shaista (Penerbit Universiti Kebangsaan Malaysia, 2020)
Un-doped CdS and Zn metal-doped CdS (0.1-0.5 M) were synthesized by chemical precipitation method. Properties like optical band gap and conductivity were determined by different characterization techniques. UV-Visible spectroscopy was applied to estimate the band gap where it showed a significant blue shift due to quantum confinement effect. Size determined by scanning electron microscopy (SEM) was found to be in nanorange from 41 to 60 nm for both un-doped and metal doped CdS nanocrystals. EDAX confirmed the doping by showing peak for Zn. XRD (X-ray diffraction) showed the lattice structure to be cubic for the synthesized nanoparticles and conductivity for un-doped CdS was 7.69E-6 Ω-1m-1 where it changes to 9.25E-6 Ω-1 m-1 and 7.98E-6 Ω-1m-1 for 0.2 M and 0.5 M Zn-doped CdS, respectively. In order to obtain good results, nanocrystals having highest conductivity are used in soft lithographic technique. Here µTM (micro transfer-molding) was followed for patterning with PDMS (poly-(dimethylsiloxane)) mold and silicon substrate for better results.